Tourism Marketing Communication Strategy For West Sumatra in Promoting Tourism Events to Increase Tourist Visits in 2023 - Yudha Pratama putra; Nurul Huda (Jurnal Pariwisata Nusantara (JUWITA), 2025)
Purpose: The West Sumatra Provincial Government launched "Visit Beautiful West Sumatra 2023," a post-pandemic activation program aimed at increasing the number of tourist visits to West Sumatra by implementing events. This study aims to analyze and understand the tourism marketing communication strategy of the West Sumatra Government in promoting the "Visit Beautiful West Sumatra 2023" program to boost tourist visits to West Sumatra. Method: The research method used is descriptive qualitative with a case study approach. The results indicate that the strategy currently employed by the West Sumatra government has been quite successful in promoting tourism events. Result: This success is reflected in the 137 percent increase in tourist visits to West Sumatra during 2023, surpassing the target of 8.2 million visitors. This study concludes that the success of this marketing communication strategy can be measured by the high number of tourists visiting West Sumatra in 2023. Contribution: The marketing communication strategy of the West Sumatra Tourism Province can serve as an example and be applied by provinces, regencies, and cities in Indonesia to increase tourist visits.